Structure Performance on the Long Span Bridge in Riau Province (Case on Siak I Bridge) - Sugeng Wiyono (JSE Journal of Science and Engineering, 2025)
Siak I Bridge is located in Pekanbaru City and was constructed in 1975 and used in April 1977. The bridge has undergone a functional change; initially, Siak I Bridge served as a Class IIA collector road but was later reclassified as a Class I arterial road. This change resulted in performance degradation due to cracking in the piers/columns, which has been repaired using grouting methods and reinforced with steel jackets. Cracks were also observed on the deck slab, and grouting has been applied to these cracks as well. Therefore, an evaluation of the bridge’s serviceability and a structural strengthening study are necessary. The methods used in structural assessment/research include Ultrasonic Pulse Velocity (UPV) testing, thickness test, rebar scanning, dynamic loading test and frequency testing. These tests aim to verify the bridge’s serviceability capacity. Based on the vibration frequency tests conducted on the bridge, there are three points where the actual vibration frequencies are lower than the theoretical natural frequencies. Meanwhile, thirteen other points show actual frequencies exceeding the natural frequencies. Hence, the structural health condition of Siak I Bridge comprises both healthy and unhealthy sections. Strengthening or repair was suggested on the unhealthy parts